2016
DOI: 10.1098/rsta.2015.0215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the March 2015 solar eclipse on near-surface atmospheric electricity

Abstract: Measurements of atmospheric electrical and standard meteorological parameters were made at coastal and inland sites in southern England during the 20 March 2015 partial solar eclipse. Clear evidence of a reduction in air temperature resulting from the eclipse was found at both locations, despite one of them being overcast during the entire eclipse. The reduction in temperature was expected to affect the near-surface electric field (potential gradient (PG)) through a reduction in turbulent transfer of space cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This is partly consistent with results from the 11 August 1999 eclipse over southeast England where decreased convection was observed and convective cloud dissipated [23]. However, Bennett [15] concluded that the reduction in turbulence was insufficient to influence the surface atmospheric electric field.…”
Section: (B) Surface Meteorological Changessupporting
confidence: 84%
See 2 more Smart Citations
“…This is partly consistent with results from the 11 August 1999 eclipse over southeast England where decreased convection was observed and convective cloud dissipated [23]. However, Bennett [15] concluded that the reduction in turbulence was insufficient to influence the surface atmospheric electric field.…”
Section: (B) Surface Meteorological Changessupporting
confidence: 84%
“…[4,22]). Burt [14] and Bennett [15] analysed the wide range of measurements made at the Reading University Atmospheric Observatory, UK, where the eclipse reduced the solar radiation by 85% but the measurements were obtained under a 400 m thick layer cloud with its base at about 200 m above the surface. During the 2015 eclipse, Burt [14] found a reduction in near-surface turbulence and a reduction in cloud base height.…”
Section: (B) Surface Meteorological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The layer-cloud investigated here persisted over RUAO during 19 March 2015 (year day 78 of 2015) and dissipated after local noon on 20 March 2015. The cloud received unusually close scrutiny because it obscured the partial solar eclipse which occurred on 20 March, and the associated atmospheric electricity and meteorological conditions are extensively described in Bennett (2016) and Burt (2016) respectively. Figure 1 shows ceilometer, PG and sounding measurements made beneath the layer-cloud.…”
Section: Conditionsmentioning
confidence: 99%
“…An additional source of atmospheric electrical observations was from magnetic observatories, such as the magnetic data from the 21 August 1914 total solar eclipse compiled by Bauer and Fisk (1916), which includes atmospheric electrical and meteorological measurements. Bennett (2016) gives a more detailed account of atmospheric electrical measurements during solar eclipses.…”
Section: 41mentioning
confidence: 99%